Value Relevance of Accounting Information and Earning Management Before and After The Implementation of International Financial Reporting Standard - Astari, Ni Putu Erviani; Sukartha, I Made (E-Jurnal Akuntansi, 2017)
The benefit of the International Financial reporting standard implementation as a standard that can lead to an increase in value relevance of accounting information and a decrease in earning management.This study aimed to test whether there is any diferrence between before and after the implementation of IFRS in value relevance of accounting information and earning management in Indonesia. This study is classified for comparative research. The population are all companies that listed on the Indonesia stock exchange for 8 years (2008-2015) and the sample is determined with purposive sampling method in order to be obtained 170 companies as the sample. The data were analyzed by using multiple regression analysis for value relevance of accounting information, logistic regression analysis for timely loss recognition, wilcoxon test for earning management. The result of this study showed that the implementation of IFRS has not been able to increase the value relevance of accounting information, there is no difference of timely loss recognition, and the implementation of IFRS has decreased the earning management on all companies that listed on the Indonesia stock exchange. Based on the results, it is suggested for further research adding other variables, adding more observations years, and expanding research by doing analysis in every single industries that listed on the Indonesia stock exchange. Keyword : IFRS, financial statement, accounting earning.